ANALISIS RENCANA PELAKSANAAN PEMBELAJARAN (RPP) BIOLOGI BERKARAKTER KELAS XI SMAN UNTUK STANDARISASI RPP DIKOTA BUKITTINGGI - Meylisa, Welia - (Pendidikan Biologi, 2014)
Professional teacher is a teacher who is able to develop learning tools such as the annual program, the semester program, syllabus and lesson plan (RPP). In this case, teachers are required to design and show their professionalism in designing the lesson plan (RPP). In general, the biology teachers at XI class in SMAN Bukittinggi City no attention to the linkages between the indicators with the aim of learning in creating lesson plan (RPP). This research is aimed to determine lesson plan the standardized created by the teachers at XI class in SMAN Bukittinggi City. The research is a descriptive. Researcher only describes and interprets the data as it is. In this case, it sees from the completeness the components of lesson plan (RPP) and to analyze the relationship between the components of lesson plan (RPP). Sample is taken by random sampling. Variable in this research is a lesson plan (RPP) that there are 68.5% and 31.5% no. The average lesson plan (RPP) made by teachers at XI class in SMAN Bukittinggi City is 66, 5% with adequate criteria. From the analysis, it can be concluded that the lesson plan (RPP) which is created by teachers at XI class in SMAN Bukittinggi City SMAN is adequate standard.